2008
DOI: 10.1128/aem.02479-07
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Robust Growth of Prochlorococcus Colonies and Dilute Liquid Cultures by “Helper” Heterotrophic Bacteria

Abstract: Axenic (pure) cultures of marine unicellular cyanobacteria of the Prochlorococcus genus grow efficiently only if the inoculation concentration is large; colonies form on semisolid medium at low efficiencies. In this work, we describe a novel method for growing Prochlorococcus colonies on semisolid agar that improves the level of recovery to approximately 100%. Prochlorococcus grows robustly at low cell concentrations, in liquid or on solid medium, when cocultured with marine heterotrophic bacteria. Once the Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
317
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(334 citation statements)
references
References 29 publications
13
317
1
3
Order By: Relevance
“…Specifically, cysteine and methionine residues are especially sensitive to ROS (Arts et al, 2015). Although heterotrophic bacteria, including some Alteromonas strains, may scavenge ROS and thus reduce potential oxidative stress affecting Prochlorococcus (Morris et al, 2008;Morris et al, 2011), other marine heterotrophic bacteria, again including Alteromonads, in fact produce extracellular superoxide (Diaz et al, 2013). Additionally, the killing mechanism of many antibiotics ultimately involves the generation of ROS (reviewed by Dwyer et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, cysteine and methionine residues are especially sensitive to ROS (Arts et al, 2015). Although heterotrophic bacteria, including some Alteromonas strains, may scavenge ROS and thus reduce potential oxidative stress affecting Prochlorococcus (Morris et al, 2008;Morris et al, 2011), other marine heterotrophic bacteria, again including Alteromonads, in fact produce extracellular superoxide (Diaz et al, 2013). Additionally, the killing mechanism of many antibiotics ultimately involves the generation of ROS (reviewed by Dwyer et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Although significant advances have been made in understanding 'top down' control of Prochlorococcus populations by phage and grazers (for example, Worden and Binder, 2003;Avrani et al, 2011;Pasulka et al, 2015), as well as 'bottom up' control by nutrients, temperature and light (for example, Bouman et al, 2006;Johnson et al, 2006;Saito et al, 2014), studying how co-occurring heterotrophic microbes affect Prochlorococcus is still in its infancy. Several recent studies have shown that co-occurring heterotrophic bacteria can both enhance and inhibit the growth of Prochlorococcus in laboratory co-cultures (Morris et al, 2008;Sher et al, 2011). Furthermore, such interactions may have significant effects on the viability of Prochlorococcus in the oceans, for example through scavenging by heterotrophic bacteria of reactive oxygen species (ROS) produced by Prochlorococcus (Morris et al, 2011(Morris et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…N. yellowstonii and N. gargensis, the two cultivated thermophilic strains of AOA, also could not be established in pure culture (Hatzenpichler et al, 2008;de la Torre et al, 2008). This may be because there is a cooperative relationship between the bacteria and the archaea in these enrichment cultures, as has been reported in cultures of the marine chlorophyte Prochlorococcus (Morris et al, 2008), and low cell density dilutions that do not contain the associated heterotrophic bacteria are unable to grow. Interactions between the heterotrophic bacteria and autotrophic archaea in the enrichment, and in the ocean, will be an exciting area of future research.…”
Section: Phylogenymentioning
confidence: 94%
“…Bulk chlorophyll fluorescence and flow cytometry samples were collected daily to monitor cell abundance; Prochlorococcus were counted based on chlorophyll fluorescence, and heterotrophs were enumerated following SYBR staining. The purity of axenic NATL2A cultures was verified before and after the experiment by testing for growth in three purity broths (ProAC, ProMM and MPTB (Saito et al, 2002;Morris et al, 2008;Berube et al, 2015)) and by flow cytometry. Transcriptome samples were collected by removing 10 ml of culture and placing it immediately into 30 ml of cold RNALater, then incubating these samples for 1-3 days at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Growth of Prochlorococcus-the numerically dominant phytoplankter in the world's oceans (Flombaum et al, 2013)-in culture is improved by the presence of certain heterotrophs in terms of longevity, stationary phase cell density and ability to grow from low cell density (Sher et al, 2011). This phenomenon is attributable at least in part to the role of heterotrophs in reducing the levels of toxic reactive oxygen species such as hydrogen peroxide (Morris et al, 2008(Morris et al, , 2011. This is thought to compensate for the absence of catalase in the Prochlorococcus genome, indicating that interspecies interactions have clearly influenced the evolutionary selective pressures and processes acting upon this group of organisms (Morris et al, 2012).…”
Section: Introductionmentioning
confidence: 99%